Retinaldehyde dehydrogenase 2 (RALDH2)- independent patterns of retinoic acid synthesis in the mouse embryo - Niederreither, Karen (National Academy of Sciences, 2002)
Knockout of the murine retinoic acid (RA)-synthesizing enzyme retinaldehyde dehydrogenase 2 (RALDH2) gene leads to early morphogenetic defects and embryonic lethality. Using a RA-responsive reporter transgene, we have looked for RA-generating activities in Raldh2-null mouse embryos and investigated whether these activities could be ascribed to the other known RALDH enzymes (RALDH1 and RALDH3). To this end, the early defects of Raldh2(−/−) embryos were rescued through maternal dietary RA supplementation under conditions that do not interfere with the activity of the reporter transgene in WT embryos. We show that RALDH2 is responsible for most of the patterns of reporter transgene activity in the spinal cord and trunk mesodermal derivatives. However, reporter transgene activity was selectively detected in Raldh2(−/−) embryos within the mesonephric area that expresses RALDH3 and in medial-ventral cells of the spinal cord and posterior hindbrain, up to the level of the fifth rhombomere. The craniofacial patterns of RA-reporter activity were unaltered in Raldh2(−/−) mutants. Although these patterns correlated with the presence of Raldh1 and/or Raldh3 transcripts in eye, nasal, and inner ear epithelia, no such correlation was found within forebrain neuroepithelium. These data suggest the existence of additional RA-generating activities in the differentiating forebrain, hindbrain, and spinal cord, which, along with RALDH1 and RALDH3, may account for the development of Raldh2(−/−) mutants once these have been rescued for early lethality.